PENGARUH WORD OF MOUTH (WOM), KUALITAS PRODUK DAN PEMASARAN DIGITAL TERHADAP MINAT BELI ULANG BAKSO MAK CI BIREUEN - Dwi Sultan, Muhammad; Izzah, Nurul; Jannah, Raudhatul (JURNAL KEBANGSAAN, 2023)
The study aims to analyze the influence of word of mouth, product quality, and digital marketing on consumer repurchase intentions at Bakso Mak Ci Bireuen. The quantitative method used was a survey approach with 96 respondents. Data were collected through a questionnaire. The results of the regression analysis showed that partially, word of mouth did not have a significant influence on repurchase intentions. In contrast, product quality and digital marketing had a significant partial influence on repurchase intentions. Simultaneously, the three independent variables significantly influenced repurchase intentions with a contribution of 50.3%